Atmospheric models applied to DGPS and RTK network in Brazil: Preliminary results - Monico, J. F.G. [UNESP]; Alves, D. B.M. [UNESP]; Dalbelo, L. F.A. [UNESP]; Camargo, P. O. [UNESP]; Sapucci, L. F.; Fortes, Luiz Paulo Souto (My University, 2006)
Several positioning techniques have been developed to explore the GPS capability to provide precise coordinates in real time. However, a significant problem to all techniques is the ionosphere effect and the troposphere refraction. Recent researches in Brazil, at Sao Paulo State University (UNESP), have been trying to tackle these problems. In relation to the ionosphere effects it has been developed a model named Mod_Ion. Concerning tropospheric refraction, a model of Numerical Weather Prediction (NWP) has been used to compute the zenithal tropospheric delay (ZTD). These two models have been integrated with two positioning methods: DGPS (Differential GPS) and network RTK (Real Time Kinematic). These two positioning techniques are being investigated at São Paulo State University (UNESP), Brazil. The in-house DGPS software was already finalized and has provided very good results. The network RTK software is still under development. Therefore, only preliminary results from this method using the VRS (Virtual Reference Station) concept are presented.